Scientometric Analysis of Biofilm Research in Microbial Fuel Cells: Insights into Key Research Areas and Emerging Trends - Christwardana, Marcelinus; Suedy, Sri Widodo Agung; Harmoko, Udi (Eksergi, 2024)
A scientometric investigation mapped the literature on biofilm development in Microbial Fuel Cells (MFCs), revealing promising renewable energy prospects and waste treatment solutions. The analysis encompassed 16898 sources, predominantly research articles (12571), along with review papers, conference papers, books, and other publications. Network analysis highlighted key research clusters and subtopics, including biofilm characterization, electrode optimization, and monitoring/control technologies. Insights from biofilm research have led to innovative approaches like biofilm engineering and advanced analytical techniques, enhancing real-world applications. Integration of MFCs into sustainable development underscores biofilms' potential as eco-friendly and economically viable components of energy production systems.